Cover Image, Volume 38, Issue 4. Issue 4 (April 2017) - Pannone, Luca; Bocchinfuso, Gianfranco; Flex, Elisabetta; Rossi, Cesare; Baldassarre, Giuseppina; Lissewski, Christina; Pantaleoni, Francesca; Consoli, Federica; Lepri, Francesca; Magliozzi, Monia; Anselmi, Massimiliano; Delle Vigne, Silvia; et al.
Abstract : On the cover : The cover image, by Luca Pannone et al., is based on the Research Article Structural, Functional, and Clinical Characterization of a Novel PTPN11 Mutation Cluster Underlying Noonan Syndrome, Pages 451–459. DOI10.1002/humu.23175